Ambivalent Visual Representations of Robert 'the Wise' in Occitan Illustrated Texts. (3rd April 2017) - Léglu, Catherine
Abstract: Art historians have long studied the Italian Angevins' combination of Franciscan devotion and dynastic propaganda. This article examines two Occitan texts that contain unusual images of King Robert 'the Wise'. The illustrations of both works are genealogical and they reflect the dispute over the competing claims of Robert and his nephew Carobert over the throne of Naples. In both texts, the lineage of Hungary is accorded an important role. It is argued that this is a reflection of the Italian Angevins' use in Provence of the lineage of Hungary to justify their authority as that of a 'blessed line' of kings and saints.